Bharat: a resurgence of the Hindu Spirit - Sangameswaran, K. V. (Chennai Clever Fox Publishing, 2024)
his work is divided into two volumes. The first volume deals with epochal changes which transformed the destiny of the Hindu civilization forever beginning with the downfall of Hindu India. This gory period has been vividly presented in a separate chapter in Volume 1. Prior to the recurrent Muslim invasions, India has always had a virile democratic construct epitomized by the structures of its society and polity. Democratic construct therefore is neither new nor unknown to the Indians and is thus not a colonial import as is made out to be. Volume 1, in addition, contains a brief sketch on the philosophy of the Hindu civilization. The chapter on Hindu Nationalism highlights the need for the development of a national consciousness, a sentiment projected as a war cry by Savitri Devi. The chapter on Tamil nationalism chronicles the evolution of the Dravidian movement which was heavily sponsored by the British colonial system and Christian missionaries. By the time this parochially divisive movement had taken roots, there was a period which saw frenetic proselytizing activities of the Christian missionaries. It must be said to the credit of the colonials that they, in all fairness, allowed for both a physical and ideological battle to be waged by the Hindus.
Keywords: Hindu Civilization